Is It a Tumor or Not? A Case of Focal Segmental Glomerulosclerosis Secondary to Type 2 Diabetes with a Concomitant Renal Pseudotumor - Rery TF Yuniarti; Ian Effendi; Zulkhair Ali; Novadian; Suprapti; Elfiani; Novandra AP; Dila Siti Hamidah; Fadil Pramudhya Husein; Ika Kartika Edi P (HM Publisher, 2024)
Background: Focal segmental glomerulosclerosis (FSGS) is a histologic pattern of glomerular injury that can be primary or secondary to various conditions, including obesity, diabetes, and hypertension. Renal masses, often detected incidentally, can be benign or malignant, with renal cell carcinoma (RCC) being the most common. This case report presents a patient with FSGS secondary to type 2 diabetes and a concomitant renal pseudotumor, initially suspected to be RCC. Case presentation: A 60-year-old woman presented with weakness, fever, and weight loss. Imaging revealed a renal mass, initially suspected to be RCC. A kidney biopsy revealed FSGS, and further evaluation confirmed type 2 diabetes. After controlling her diabetes and hypertension, the renal mass regressed, suggesting a pseudotumor. Conclusion: This case highlights the importance of considering pseudotumors in the differential diagnosis of renal masses, especially in patients with comorbidities such as diabetes. A kidney biopsy can help avoid unnecessary invasive procedures like nephrectomy.